2006
DOI: 10.1111/j.1365-2699.2006.01586.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: How many species of shore fishes are there in the Tropical Eastern Pacific?

Abstract: Aim  To assess whether the total richness of the shore‐fish fauna of a discrete biogeographical region can be predicted, and to estimate how long it is likely to take to enumerate that fauna. Location  The Tropical Eastern Pacific (TEP), an isolated biogeographical region with a high level of endemism (72%) among its modestly rich, known fauna of shore fishes (1222 named + 58 known undescribed shallow‐water species). Methods  We used patterns in the long‐term dynamics and accumulation curves of descriptions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 51 publications
(69 reference statements)
0
64
0
12
Order By: Relevance
“…Particularly species that attain small body sizes have been underestimated in the TEP, and possible undiscovered species might belong to this group of species (Zapata & Robertson, 2007). During this study we found four new records of species for Gorgona island (Chriolepis cuneata, Gobulus crescentalis, Cosmocampus arctus, Canthigaster janthinoptera), three of which are secretive or cryptic and represent southward range extensions in the TEP (Alzate, Muñoz, Zapata & Giraldo, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Particularly species that attain small body sizes have been underestimated in the TEP, and possible undiscovered species might belong to this group of species (Zapata & Robertson, 2007). During this study we found four new records of species for Gorgona island (Chriolepis cuneata, Gobulus crescentalis, Cosmocampus arctus, Canthigaster janthinoptera), three of which are secretive or cryptic and represent southward range extensions in the TEP (Alzate, Muñoz, Zapata & Giraldo, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Systems such as these are useful for managers, biologists, students, and fi shers wanting to identify fi shes and obtain information about their biology. The information that systems such as this bring together allows comprehensive assessments of our level of knowledge about biodiversity (Zapata and Robertson, 2006) and regional geographic distribution of that diversity (Mora and Robertson, 2005;Robertson and Cramer, 2009). …”
Section: Online Information System On Tropical Eastern Pacific Shorefmentioning
confidence: 99%
“…Analyses of particular taxa or functional groups have shown that wide-ranging or conspicuous species are discovered earlier than small species or those with narrow ranges (Gaston et al, 1995;Allsopp, 2003;Collen et al, 2004;Stork et al, 2008). The extent to which this bias is a phenomenon in the marine realm has so far only been tested for zooplankton and coastal fish species in the tropical eastern Pacific (Gibbons et al, 2005;Zapata and Robertson, 2007). In both cases rates of species description showed similar trends to those found in terrestrial environments.…”
Section: Introductionmentioning
confidence: 96%